2021
DOI: 10.1088/1361-6528/ac1540
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical application of graphitic carbon nitrides: tissue deposition in vivo, induction of reactive oxygen species (ROS) and cell viability in tumor cells

Abstract: The urgency for new materials in oncology is immediate. In this study we have developed the g-C3N4, a graphitic-like structure formed by periodically linked tris-s-triazine units. The g-C3N4 has been synthesized by a simple and fast thermal process. XRD has shown the formation of the crystalline sheet with a compacted structure. The graphite-like structure and the functional groups have been shown by Raman and FTIR spectroscopy. TEM image and AFM revealed the porous composed of five or six C–N layers stacked. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The IR bands noticed at 1650 cm -1 and at 3572 cm -1 can be related to the H-O-H bending vibration of H 2 O and -OH stretching vibrations of adsorbed H 2 O molecules on the surface, respectively (13). For GCN, the out-of-plane bending vibration, which is characteristic of triazine or heptazine units appears at 809 cm -1 while the IR band at 879 cm -1 is attributed to the bending vibration of N-containing heterocycles (14). The stretching vibrations of C-NH-C are observed at 1247 cm -1 , 1323 cm -1 while the stretching vibrations of C═ N and C═C in the s-triazine ring are noticed at 1647 cm -1 and 1556 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The IR bands noticed at 1650 cm -1 and at 3572 cm -1 can be related to the H-O-H bending vibration of H 2 O and -OH stretching vibrations of adsorbed H 2 O molecules on the surface, respectively (13). For GCN, the out-of-plane bending vibration, which is characteristic of triazine or heptazine units appears at 809 cm -1 while the IR band at 879 cm -1 is attributed to the bending vibration of N-containing heterocycles (14). The stretching vibrations of C-NH-C are observed at 1247 cm -1 , 1323 cm -1 while the stretching vibrations of C═ N and C═C in the s-triazine ring are noticed at 1647 cm -1 and 1556 cm -1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Controversially, Wigner et al (2021) evaluating the influence of polymeric nanoparticles (PLA/ MMT/TRA, PLA/EDTMP, PLGA/MDP, and Pluronic F127 Ms) on the cell, homeostasis demonstrated that all nanosystems were able to produce a toxic effect, which included: genotoxicity effect by internucleosomal DNA fragmentation and formation of ROS. In the same way, Freire et al (2021), studying the biomedical application of graphitic carbon nitrides nanoparticles, found that although graphitic carbon nitrides may induce cell apoptosis, the mechanism was not by the formation of ROS formation.…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 90%
“…Many in vitro and in vivo studies have shown that exposure to nanoparticles could induce the production of reactive oxygen species (ROS). ROS generation is directly related to alteration in mitochondrial metabolism, which represents one of the main markers confirming apoptosis induction since ROS causes oxidative stress, inflammation, and subsequent damage to proteins, cell membranes, and DNA (Huang et al 2017;Freire et al 2021;Wigner et al 2021).…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…Nanoscale drug delivery systems offer advantages due to their biocompatibility, non-toxicity, and nonimmunogenicity [ 10 , 11 , 12 ]. These systems can be targeted to the tumor site, increasing bioavailability and allowing the transportation of multiple drugs or molecules to the tumor [ 13 ].…”
Section: Introductionmentioning
confidence: 99%